The Impact of Youth Red Cross Extracurricular Activities on Humanitarian Attitudes of Students at MTsN 1 Nganjuk - Inayah, Denik; Pertiwi, Desy Edkhonanda Kusuma; Barkah, Ika; Rusmayani, Rusmayani; Paisun, Paisun (STAI Miftahul Ula Nganjuk, 2024)
The objectives of this study were, To describe the Youth Red Cross extracurricular activities at MTsN 1 Nganjuk, To assess the current state of humanitarian attitudes among the students, To determine the influence of the Youth Red Cross extracurricular activities on the students' humanitarian attitudes. The research employed a correlational quantitative method with a hypothesis-driven approach. The population consisted of 7th and 8th-grade students who were members of the Youth Red Cross. The research variables were the Youth Red Cross extracurricular activities (independent variable, X) and students' humanitarian attitudes (dependent variable, Y). Data collection techniques included observation, interviews, questionnaires, and documentation. The data were analyzed using Karl Pearson's Product-Moment correlation formula. The findings indicated that the Youth Red Cross extracurricular activities have been effectively implemented and have shown considerable development, as evidenced by the high number of participants and the achievements earned, there has been a significant decline in the humanitarian attitudes of students, primarily due to the COVID-19 pandemic and the influence of social media, the Youth Red Cross extracurricular activities have a significant impact on the humanitarian attitudes of students at MTsN 1 Nganjuk, as demonstrated by the correlation coefficient (r = 0.817), indicating a strong positive influence